Frecuencia De Parásitos Gastrointestinales En Cobayos (Cavia Porcellus). Atendidos En La Clínica Veterinaria Pet Company En Bogotá - Colombia (2021)
The present study was carried out to determine the frequency of gastrointestinal parasites in clinically healthy guinea pigs (Cavia porcellus) in patients treated at the Pet Company veterinary clinic in Bogotá, as well as to identify the gender of the parasites found and determine possible zoonoses. The methodology used was the collection of fecal samples from guinea pigs (Cavia porcellus) that were taken to the Pet Company clinic by the guardians of the patients and delivered to the responsible clinician. 14 samples were collected, which were processed by flotation methods with hypersaturated solutions and direct smear, obtaining 78.57% (11/14) positive cases and 21.42% (3/14) negative cases, of gastrointestinal parasitosis. The identified parasites were Giardia sp 63.63% (7/14), Eimeria sp 54.54% (6/14) and Entamoeba sp 9.09% (1/14). Of these Giardia sp and Entamoeba sp, were the species found with possible zoonoses. In general, the frequency of gastrointestinal parasites in the pets studied and the production animals found in the literature review differed in the presence of pathogenic parasites such as Paraspidodera sp, Passarulus sp, Cryptosporidium sp and Trichuris sp, which were not found in the present study.